Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Cooperative Learning Tipe Scramble Di Kelas V Sekolah Dasar - Hardi, Yola Nabila; Zuryanty, Zuryanty (Indo-MathEdu Intellectuals Journal, 2024)
This research is based on the low learning outcomes of students. The purpose of this study is to describe the improvement of learning outcomes using the Scramble type Cooperative Learning model in grade V of SDN 35 Tanjung Bonai, Tanah Datar Regency. This research is classroom action research that uses qualitative and quantitative approaches. The research was carried out in two cycles, namely cycle I was held 2 meetings and cycle II was carried out 1 meeting. The results of the study showed an increase in: a) RPP cycle I with an average of 84.72% (B), cycle II 94.44% (SB), b) Implementation in the educator aspect of cycle I with an average of 83.33% (B), cycle II 91.66% (SB), while implementation in the student aspect of cycle I with an average of 79.16% (B), cycle II 91.66% (SB), c) Assessment of students in improving learning outcomes in cycle I meeting 1 aspect of spiritual attitude there was 1 student with outstanding positive behavior and aspect Social There are 2 students with prominent positive behavior. In the first cycle of meeting 2 on the aspect of spiritual attitudes, there were 2 students with prominent positive behavior and 2 students with prominent positive behavior. Then in the second cycle in the aspect of spiritual attitudes, there were 2 students who behaved prominently and in the social aspect, there were 2 students who behaved prominently. As for the knowledge aspect of the first cycle, an average of 79.09 was obtained and the second cycle averaged 91.36, and in the skill aspect of the first cycle an average of 77.69 and the second cycle 87.78